2021
DOI: 10.3390/ijerph18020573
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Environmental Metal Exposure and Preterm Birth: A Scoping Review

Abstract: Preterm birth (PTB) and its complications are the leading causes of under-five year old child deaths, accounting worldwide for an estimated one million deaths annually. The etiology of PTB is complex and multifactorial. Exposures to environmental metals or metalloids are pervasive and prenatal exposures to them are considered important in the etiology of PTB. We conducted a scoping review to determine the extent of prenatal exposures to four metals/metalloids (lead, mercury, cadmium and arsenic) and their asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 89 publications
2
26
0
Order By: Relevance
“…More importantly, the comparison between the two cities showed that patients from Petrosani, a well-known industrial region, had higher concentrations of Zn, Cd, Pb and As. This is in agreement with other international studies showing that people living in industrialized regions are susceptible to accumulation of these elements, even if they mostly measured the concentrations either in the mother's serum, urine, toe-nails, hair, fetal placenta and cord blood ( 16-22 , 90 , 115 , 120 , 121 ). These elements are important as their concentration may be further increased by tobacco and are secreted in colostrum and breast milk ( 122 ).…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, the comparison between the two cities showed that patients from Petrosani, a well-known industrial region, had higher concentrations of Zn, Cd, Pb and As. This is in agreement with other international studies showing that people living in industrialized regions are susceptible to accumulation of these elements, even if they mostly measured the concentrations either in the mother's serum, urine, toe-nails, hair, fetal placenta and cord blood ( 16-22 , 90 , 115 , 120 , 121 ). These elements are important as their concentration may be further increased by tobacco and are secreted in colostrum and breast milk ( 122 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, nickel (Ni) was associated with higher birth weight, suggesting different metals have different effects on fetal development. Several previously reported studies support our observed associations ( 17 , 19 22 ). Because of the abundance of lipids in the body, particularly in the placenta, lipidomics has the potential to serve as a powerful tool to predict adverse birth outcomes by characterizing lipid profiles.…”
Section: Introductionsupporting
confidence: 93%
“…In the specific case of IUGR, a dosage of antioxidant molecules (glutathione, SOD, Glutathione peroxidases) in a 2009 study did not associate OS parameters with low birth weight [ 49 ] under exposure to metals that were systematically measured in this last study in the placenta, by instrumental neutron activation analysis (INAA), i.e., Zn, Hg, Se and As, and by atomic absorption spectrometry (AAS), i.e., Fe, Cu, Cd. In the case of preterm birth, by contrast, a recent review [ 50 ], based upon the cross-analysis of 36 articles, showed that there is a higher incidence of the disease under exposure to Pb and Cd, while the results were inconclusive for Hg and As.…”
Section: Mechanisms Of Oxidative Stress Induction By Environmental Pollutantsmentioning
confidence: 99%